2021
DOI: 10.1039/d1ra02116h
|View full text |Cite
|
Sign up to set email alerts
|

Probing protein dissociation from gold nanoparticles and the influence of temperature from the protein corona formation mechanism

Abstract: A protein corona changes protein's structure and characteristics, hindering their identification in situ. Dissociation is an important solution to identify their composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…To this end, SERS was found useful to probe the dissociation of thio-proteins, with stable Au−thiol bond, versus nonthio-proteins from Au NPs. 90 SERS measurements also enable the tracking of possible conformational changes of protein molecules following surface adsorption to Au NPs. 89,91 It was shown that thio-protein sulfhydryl groups on HSA form Au−thiol covalent bonds resulting in changes in the secondary structure of HSA as indicated by SERS measurements.…”
Section: K Pmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, SERS was found useful to probe the dissociation of thio-proteins, with stable Au−thiol bond, versus nonthio-proteins from Au NPs. 90 SERS measurements also enable the tracking of possible conformational changes of protein molecules following surface adsorption to Au NPs. 89,91 It was shown that thio-protein sulfhydryl groups on HSA form Au−thiol covalent bonds resulting in changes in the secondary structure of HSA as indicated by SERS measurements.…”
Section: K Pmentioning
confidence: 99%
“…Based on the currently accepted hypothesis, soft PC formation is a reversible process that involves protein adsorption to the surface of NPs followed by dissociation whereas hard PC formation is an irreversible process. To this end, SERS was found useful to probe the dissociation of thio-proteins, with stable Au–thiol bond, versus nonthio-proteins from Au NPs . SERS measurements also enable the tracking of possible conformational changes of protein molecules following surface adsorption to Au NPs. , It was shown that thio-protein sulfhydryl groups on HSA form Au–thiol covalent bonds resulting in changes in the secondary structure of HSA as indicated by SERS measurements .…”
Section: Spectroscopic Techniques and Theoretical Models To Investiga...mentioning
confidence: 99%
“…When nanomaterials are exposed to biological fluids (e.g., HP, urine, saliva, gastrointestinal fluids, etc. ), they become coated by a protein layer, referred to as the protein corona [25], whose composition is shaped by a complex interplay between the chemical-physical properties of the nanomaterial (e.g., size and surface charge [26]), the protein source (e.g., human plasma and its concentration [27]) and "environmental factors", such as temperature [28], incubation time [29], and shear stress [30]. A series of papers by our group [10,31] demonstrated that the nanoparticle-protein corona is disease-specific, and personalized.…”
Section: Discussionmentioning
confidence: 99%
“…The PC of AuNPs is stabilized by the covalent bonds of thio-proteins such as β-lactoglobulin, which comprise the hard PC, or the electrostatic interactions of non-thio-proteins such as myoglobin, which comprise the soft PC. 127 Temperature has a major role, specifically in the adsorption of the thio-proteins. Although increasing the temperature decreases the binding forces and the number of adsorbed β-lactoglobulin, it results in a faster thiol covalent bond formation in the β-lactoglobulin PC of AuNPs.…”
Section: E Effect Of Temperature and Shear Flowmentioning
confidence: 99%
“…[146][147][148][149][150] Gold forms Au-thiol covalent bonds with proteins due to its high affinity for thiols. 127,151 Also, it interacts with proteins via electrostatic forces. Given the extensive use of AuNPs for biomedical purposes, a growing body of studies has investigated the interaction of AuNPs with proteins as it relates to the fate of AuNPs as well as their in vivo toxicity.…”
Section: A Gold Nanoparticlesmentioning
confidence: 99%